The Analysis of Factors Influencing Incidence Rates of Toddler Pneumonia in Purwakarta Districts Using Panel Data Spatial Regression - Nadiyah Nisrina; Budhi Handoko; Yudhie Andriyana (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
Pneumonia is an acute respiratory infection that attacks the lungs and can cause inflammation of the air sacs due to the alveoli is filled with pus and fluid. This research aims at identifying factors influencing pneumonia and mapping its incidence rate for toddlers in the Purwakarta Regency. Many factors influence pneumonia, but due to the limitation of data or information, some factors cannot be included in the model and are called omitted variables. The incidence rate of toddler pneumonia in sub-districts of Purwakarta Regency is assumed to be related to one another or have a spatial dependency. Therefore, modeling pneumonia with the Fixed Effect Spatial Model can accommodate spatial aspects. The results show that MR2 measles immunization, low birth weight, exclusive breastfeeding, and clean and healthy living habits significantly affect the incidence rate of toddler pneumonia. Based on the mapping results, Wanayasa sub-district has a high incidence rate of toddler pneumonia, while some sub-districts such as Campaka, Pondoksalam, and Darangdan have low incidence rates.